Islamic Perspectives on Fulfilling Husband's Financial Responsibilities: Insights from Ulama Mazhab and Detained Citizenship - Ali, Yusuf Faisal (IAIN Manado, 2023)
This article explains the fulfillment of the husband's income as a fostered citizen in the detention center and analyzes how Islamic law reviews the implementation of the husband's income in various perspectives of ulama mazhab; in this article, the author quotes the views of Imam Hanafi, Imam Shafi'I, and Imam Maliki, in addition to some views of other scholars such as Sayyid Sabiq. This research uses literature research methods. Data were obtained by analyzing texts in books and books and legal studies. The data is analyzed in a qualitative descriptive way. The results of this study show that in Islamic law with a variety of views of imams of the madhab, including Imam Shafi'I, Maliki, and Hanafi, have the same view about fulfilling the obligation to provide for husbands who are prison-assisted citizens, husbands who are in prison are still obliged to provide for their wives according to their ability.